Measuring the Corrosion Rate of Aluminum by Using Ultra Thin Layer Activation Technique - I. Kambali; H. Suryanto; Parwanto Parwanto (PPIKSN-BATAN, 2005)
Corrosion rate of aluminum (99.9% purity) in 0.001 M hydrochloride acid solution has been measured by using Ultra Thin Layer Activation (UTLA) technique. Iron foil of 25 μm thickness was used as the primary target and activated by 10.2 MeV proton beam coming from BATAN’s cyclotron with irradiation dose of 0.73 μAh (9.534 x 1015 protons/cm2). Radioisotope 56Co formed on the foil would have sufficient kinetic energy to run out of the foil’s surface and be implanted on the aluminum used as the secondary target. After 2 days of cooling down, about 0.397 MBq of 56Co stayed on the foil was counted by NaI(Tl) detector coupled with Multi Channel Analyzer (MCA).It was found that about 9.45% of the total 56Co formed on the iron foil was successfully implanted into aluminum target. Corrosion test of aluminum was conducted in a 2 inches diameter pipe filled with 0.001 M hydrochloride acid flowing with a rate of 80 liters/minute. The corrosion rate of the aluminum was determined from the change of 56Co activity during the process. The result of experiment indicated that the sample was corroded with a very slow rate of 0.064 nm/minute and 0.0054 nm/minute for measuring time of 0-180 and 180-300 minutes respectively.